Risk for osteopenia and osteoporosis in institution-dwelling individuals with intellectual and/or developmental disabilities. (January 2015) - Lin, Lan-Ping; Hsu, Shang-Wei; Yao, Chung-Hui; Lai, Wei-Ju; Hsu, Pei-Jung; Wu, Jia-Ling; Chu, Cordia M.; Lin, Jin-Ding
Highlights: To investigate the prevalence of and contributing factors to osteopenia and osteoporosis among people with ID or/and DD. 46.2% of cases were normal and that 27.7% and 26.1% of cases had osteopenia and osteoporosis. Gender, age and body weight were associated with osteoporosis prevalence. Future initiatives need to pay much attention to the potential risk factors for bone quality. Abstract: The purpose of this study was to investigate the prevalence of and contributing factors to osteopenia and osteoporosis among people with intellectual disabilities (ID) or/and developmental disabilities (DD) residing in a disability institution in Taiwan. The present study was conducted at one disability institution in Taiwan and recruited 184 institutionalized residents with ID and/or DD (115 men and 69 women aged 18–72 years) for analysis. For all residents with ID and/or DD, information was obtained about their age, gender, level of ID, BMI, and bone mineral density (BMD). BMD is a measurement of calcium levels in bones that can estimate the risk of osteoporosis and bone fractures. Bone tests were divided into three outcome categories based on their calcaneal BMD T -scores: Normal BMD, a T -score ≧ −1; Osteopenia, −2.5 ≦  T -score < −1; and Osteoporosis, a T -score < −2.5. The results revealed that 46.2% of cases were normal and that 27.7% and 26.1% of cases had osteopenia and osteoporosis, respectively. Multiple logistic regression analyses found that male gender (OR = 2.482, 95% CI = 1.04–5.93, p  < 0.05), age ≧ 40 years (OR = 3.051, 95% CI = 1.07–8.69, p  < 0.05) and being overweight/obese (OR = 0.395, 95% CI = 0.17–0.93, p  < 0.05) were more likely to be associated with osteoporosis. Another model indicated that males (OR = 2.169, 95% CI = 1.12–4.19, p  < 0.05) and those aged ≧ 40 years (OR = 3.026, 95% CI = 1.32–7, p  < 0.01) tended to have an increased risk for osteopenia and osteoporosis. To improve the bone quality of individuals with ID or/and DD and to decrease the occurrence of osteopenia and osteoporosis, this study highlights that we should pay much attention to the potential risk factors for bone quality in these vulnerable populations.